The diversity and physiological activities of weeds in land cultivated with various corn cultivars and fertilized with various nitrogen doses - MUJI RAHAYU; PRAPTO YUDONO; DIDIK INDRADEWA; EKO HANUDIN (Society for Indonesian Biodiversity, 2019)
Abstract. Rahayu M, Yudono P, Indradewa D, Hanudin E. 2019. The diversity and physiological activities of weeds in land cultivated with various corn cultivars and fertilized with various nitrogen doses. Biodiversitas 20: 622-628. Both weeds and corn have nutrient needs. Nitrogen is one of the essential elements required by weeds and corn. Each corn cultivar and weed also has different ability to absorb nitrogen. This study aimed to determine the effect of corn cultivar and nitrogen dose on the diversity and physiological activities of weeds. The research was conducted in Banguntapan, Bantul, Yogyakarta from December 2016 to May 2017. The study used a completely randomized block design with 2 factors with three replications. The first factor was corn cultivar, consisting of four cultivars (Bisi 18, NK 33, DK 95 and Sukmaraga) and the second factor was the nitrogen dose, consisting of three levels (25 kg N ha-1, 150 kg N ha-1 and 275 kg N ha-1). The data were analyzed using 5% variance analysis and continued with Duncan test at 5% level. The results showed that the most commonly found weeds were broadleaves, but the most dominant weed was a grass, namely Dactyloctenium aegyptium, except Sukmaraga with nitrogen doses of 25 kg ha-1 and 150 kg ha-1 in 4 weeks after planting (WAP). In 8 WAP, weeds that grew in land planted with all combinations of cultivars and nitrogen doses were Cyperus rotundus, Dactyloctenium aegyptium, Digitaria ciliaris, Eleusine indica, Eragrostis tenella, Amaranthus spinosus, and Richardia scabra. There were no significant differences on the nitrate reductase activity, chlorophyll content, leaf area index, and dry weight among cultivars. The treatment of 25 kg N ha-1 resulted in the lowest leaf area index and total chlorophyll content, but the highest nitrate reductase activity.